Recognizing the Character of Children with Special Needs Through Digital Motif Design Using the Visual Language Method - Roos Nagara, Martien; Ananta, Dede (Mudra : jurnal seni budaya, 2025)
Every individual, including children with special needs, possesses creative potential that can be continually developed. This creativity is often expressed through visual media, such as images, which serve as a means of communication to convey messages, emotions, and thoughts. However, children with special needs often face unique challenges in expressing themselves, such as difficulties with verbal communication, limited motor skills, and cognitive barriers. Therefore, an inclusive and adaptive approach is essential to ensure that these children can fully express their creativity. One promising method for fostering creativity is the use of digital technology, such as Adobe Photoshop, to create digital motif designs. Through digital motif design, children with special needs can not only express themselves visually but also explore various shapes, colors, and compositions without limitations. This research aims to analyze digital motif works created by children with special needs using a visual language approach. The focus is on the objects depicted (wimba) and how they are arranged within a field (tata ungkap). Through this research, we hope to identify the personality traits of children with special needs through the interpretation of their digital motif designs. This analysis may also support the classroom learning process, provide stimulation, and enhance motivation. As a result, children’s communication, emotional expression, and abilities can be further explored. The findings of this research indicate that the use of digital media facilitate creative expression in a more inclusive and adaptive way. Thus, the artworks produced by children with special needs are not only unique and interesting but also reflect their ability to adapt and innovate despite challenges.